Abraham Lincoln [videorecording (DVD)] : preserving the Union (Biography (A & E Home Video (Firm)), 1996)
From the rustic childhood to his tragic death, this is the definitive look at the stoic president who risked everything to save his nation.Honest, eloquent and courageous, he risked everything to save a young America from self-destruction, and paid the ultimate price. This unforgettable program tells the complete story of Abraham Lincoln, from the rustic childhood that forged his beliefs to the tough campaign that made him president. Historians examine the difficult leadership choices of his turbulent first term, as well as his bouts with depression and troubled marriage to Mary Todd. Experts untangle a web of murder and kidnapping plots to learn the truth about the complex conspiracy that made Lincoln an American martyr.